Ascesa e caduta di un sodalizio mafioso tra Otto e Novecento. La sentenza Trifirò e c. (1911) - Lanfranca, Dario (Studi Politici, 2023)
In Sicily, in the first two decades after Italian Unification, the first mafias organizations appear. Between these organizations there was one criminal group from Monreale named the Stuppagghieri. In this village near to Palermo, few years after the Italian Unification, some families were particularly active in criminal activities: some elements from these families will be involved in the Stuppagghieri’s trials, some others will avoid any attentions from the police and the justice, probably because of their political protections. However, several decades after, in 1911, we’ll find the same people in a judgement of the Palermo’s Court concerning a succession of murders in Monreale. This verdict is a very important witness of the Mafia’s history also because it includes a proof of the authority of palermitain mafia above all the others organizations from the villages of the countryside.